2023
DOI: 10.1111/imj.16053
|View full text |Cite
|
Sign up to set email alerts
|

Serum ammonia does not guide management and is overutilised in patients with cirrhosis in hospital settings

Abstract: BackgroundHepatic encephalopathy is a confusional state associated with cirrhosis. Serum ammonia levels are neither sensitive nor specific for the diagnosis.AimsWe audited the ordering location and hospital unit whilst assessing the impact on management at a major Australian tertiary centre.MethodsWe conducted a single‐centre retrospective chart review of the ordering of serum ammonia levels between 1 March 2019 and 29 February 2020 at The Royal Melbourne Hospital, a tertiary‐referral centre in Melbourne, Vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…A similar situation is seen in clinical practice. Whereas a recent study demonstrated that ammonia testing during hospitalization has increased significantly from 2007 to 2015, and particularly in 2014 and 2015, these levels are not used for guiding HE treatment (30)(31). This was illustrated by a study performed on 1202 patients admitted to the hospital with HE, that aimed to evaluate the impact of ammonia levels on HE management.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A similar situation is seen in clinical practice. Whereas a recent study demonstrated that ammonia testing during hospitalization has increased significantly from 2007 to 2015, and particularly in 2014 and 2015, these levels are not used for guiding HE treatment (30)(31). This was illustrated by a study performed on 1202 patients admitted to the hospital with HE, that aimed to evaluate the impact of ammonia levels on HE management.…”
Section: Accepted Manuscriptmentioning
confidence: 99%